The Fermentation Stress Response Protein Aaf1p/Yml081Wp Regulates Acetate Production in Saccharomyces cerevisiae - Walkey, Christopher J. (Public Library of Science, 2012)

(untitled)
The production of acetic acid during wine fermentation is a critical issue for wineries since the sensory quality of a wine can be affected by the amount of acetic acid it contains. We found that the C2H2-type zinc-finger transcription factor YML081Wp regulated the mRNA levels of ALD4 and ALD6, which encode a cytosolic acetaldehyde dehydrogenase (ACDH) and a mitochondrial ACDH, respectively. These enzymes produce acetate from acetaldehyde as part of the pyruvate dehydrogenase bypass. This regulation was also reflected in the protein levels of Ald4p and Ald6p, as well as total ACDH activity. In the absence of ALD6, YML081W had no effect on acetic acid levels, suggesting that this transcription factor’s effects are mediated primarily through this gene. lacZ reporter assays revealed that Yml081wp stimulates ALD6 transcription, in large part from a GAGGGG element 590 base pairs upstream of the translation start site. The non-annotated ORF YML081W therefore encodes a transcription factor that regulates acetate production in Saccharomyces cerevisiae. We propose AAF1 as a gene name for the YML081W ORF.